Analysis Of Sharia Mortgage Financing In Puri Khazanah Regency Batang Kuis Housing At Btn Syariah In 2021-2024 - Shabira, Yusra; Yanti, Nursantri; Jannah, Nurul (Jurnal Ilmu Perbankan dan Keuangan Syariah, 2025)
This study aims to analyze the effectiveness of subsidized Sharia mortgage financing distribution carried out by BTN Syariah in Puri Khazanah Regency Batang Kuis Housing. Using qualitative descriptive methods, this study identifies and analyzes the experiences and challenges faced by customers in the sharia financing process. This study focuses on a housing complex with 40 units and the research approach through interviews with 10 selected customers, the results of the study indicate that some customers face payment difficulties that lead to bad debts, which are caused by economic instability. The conclusion of this study emphasizes the need for a more effective restructuring strategy and a more sensitive approach to the economic conditions of customers to increase the success of Sharia mortgage financing distribution. Another implication concerns the need for more intensive financial education for low-income communities, so that they understand the responsibilities and risks in mortgage financing, and have mature financial planning before making a decision to borrow. For housing developers, this study emphasizes the importance of working more closely with banks to ensure the sustainability of housing projects and customer satisfaction. Overall, this study shows that the success of the Sharia mortgage financing program depends not only on the financing agreement and structure, but also on the sensitivity of the institution to the dynamics of the community's economy. In addition, these results highlight the importance of developing more flexible and adaptive financing restructuring strategies, such as adjusting tenors or postponing installment payments under certain conditions